PENINGKATAN KAPASITAS MASYARAKAT MELALUI PROGRAM PENCEGAHAN STUNTING DI DESA LIMEHE BARAT, TABONGO KABUPATEN GORONTALO - Thalib, Tety; Katili, Andi Yusuf (Universitas Bina Taruna Gorontalo, 2024)
This devotion aims to examine efforts to increase community capacity through a stunting prevention program in West Limehe Village, Tabongo District, Gorontalo Regency. This research method is descriptive with a qualitative approach. Data collection was carried out through observation, interviews and documentation. Stunting or chronic malnutrition in children under five is a health challenge in various regions in Indonesia, including Gorontalo Regency. This program focuses on nutrition education, healthy parenting patterns, and increasing sanitation awareness. Through this outreach program, the community gains a better understanding of the importance of balanced nutrition and environmental cleanliness as an effort to prevent stunting. The research results show that increasing knowledge and community participation in preventing stunting independently and sustainably is getting better, although not yet optimal, so it needs to be improved further.